PENERAPAN GENERATED LESSON DALAM KEGIATAN LABORATORIUM BERBASIS INKUIRI UNTUK MENGUKUR KEMAMPUAN MERANCANG PERCOBAAN PADA MATERI RESPIRASI - Marlina, Reni (Universitas Tanjungpura, 2015)
The aim of this study is to measure the ability of the experimental design students PGMIPAU in the practicum General Biology.The title practicum General Biology is respiration with the implementation of inquiry based laboratory activities are generated lesson.The method used in this study was a pretest - posttest control group design. The sample in this study is a first semester student PGMIPAU the 2013/2014 school year in the practicum General Biology. The instruments used is guidance practicum, worksheet, and inquiry test by multiple choice. The results show the ability of the experimental design students PGMIPAU in the practicum General Biology with inquiry -based laboratory activities are generated lesson in the very good category is determine the type of problem have average 96%. Beside that, the ability determining purpose of the experiment in the good category with average percentage 85%. Key word: inquiry based laboratory, respiration.